Tutoria : estratégias de ensino para inclusão de alunos com deficiência em aulas de educação física - Souza, Joslei Viana de (2008)
The movement of inclusion school increasingly are entering students with disabilities in regular schools and consequently the classes of Physical Education. This proposal, including school, has been shown in practice with many difficulties such as: the non-involvement of managers in this process, lack of preparation of the teacher in their initial and continuous training, inadequate physical space to carry out the lessons; excessive number of students the classes; absence of strategies for education that will enable the effective participation of students with disabilities in classes of physical education, among others. This research has developed a work on tutoring as a strategy for education, in which a student with disabilities received help from another student during the performance of motor tasks. In this context, this research aimed to examine the effects of a training program for tutors on the participation of a student with mental disabilities associated with autism in the classes of Physical Education. It is supported by methodological assumption of feature predominantly qualitative study of the type of case. The subject of this research were: a professor of Physical Education, a student with mental disabilities associated with autism; five tutors. And interview technique were used as instruments of observation for data collection. At first there were filming the lessons of Physical Education of a school of the Network of Education Hall of Ilhéus - BA, before and after the training of tutors. The results showed that the tutoring of education as a strategy to increase the participation of students with disabilities was effective. There was involvement on the part of fellow tutors. As for the training of tutoring the data showed that more time is needed for post-training assistance from the tutors are more effective. It was concluded that the inclusion school is a utopia, but by means of draft strategies for teaching it is possible to contribute to this process if effective over time so that in future present a Physical Education for all without the need to explain in terminology of redundant Physical Education inclusive.